Hexokinase from Maize Endosperm and Scutellum - Cox, Edward L. (1973)
Hexokinase (EC 2.7.1.1) was isolated from endosperm and scutellum of developing and germinating maize (Zea mays) seeds. With fructose as the variable substate, Michaelis constant values for the scutellum enzyme were about onethird those of the endosperm enzyme (0.05 versus 0.15 mm), and no developmental differences were observed. With glucose as the variable substrate, Michaelis constant values were all in the range 0.1 to 0.2 mm. The enzyme preparation from germinating scutellum was studied further; when glucose was varied over a wide range, a Michaelis constant of 3.4 mm was observed in addition to the much lower Michaelis constant noted above. This low affinity binding of glucose may have regulatory significance and may indicate the presence of a glucokinase in addition to hexokinase.